Optimal design parameters and performance optimization of thermodynamically balanced dish/Stirling concentrated solar power system using multi-objective particle swarm optimization. (September 2020) - Zayed, Mohamed E.; Zhao, Jun; Elsheikh, Ammar H.; Li, Wenjia; Elaziz, Mohamed Abd
Highlights: An enhanced opto-geometric thermodynamic model of the solar dish/Stirling system (SDSS) was developed. MOPSO was adapted and nine decision variables were optimized to maximize overall efficiency and electric power. Contribution of each design parameter to performance optimization of SDSS was presented. A desired optimal solution was selected using LINMAP decision making method. An optimal solution with least deviation from the ideal design was obtained. Abstract: In this work, a theoretical model based on opto-geometric and thermodynamic analyses of Solar Dish-Stirling System (SDSS) considering opto-geometric sizing criteria and energy balance of different system components has been developed. An optimization algorithm has been also implemented for simultaneously maximizing the output power and total efficiency of the SDSS using the Multi-Objective Particle Swarm Optimization (MOPSO). Nine decision variables have been considered, namely, the interception factor, mirror reflectance of the concentrator, receiver absorbance, receiver transmittance, receiver emissivity, tilt angle of the receiver, the direct solar intensity, the speed of wind, and the temperature of ambient. Pareto optimal frontier (POF) was determined and the optimal solution was selected by applying a decision making approach called the Linear Programming Technique for Multidimensional Analysis of Preference (LINMAP). Moreover, a sensitivity analysis was also carried out to identify the impact of the rim angle, the dish concentrator diameter, the mirror soiling coefficient of concentrator, and the ratio of design concentration on the SDSS performance optimization. The results showed that the proposed MOPSO shows a feasible approach to achieve a maximal power output of 23.46 kW with an optimal final total efficiency of 30.15% that approaches the ideal solution. Moreover, the sensitivity results indicated that SDSS with concentrator diameters of (2.5–15 m) can produce final optimal output powers of (1.43–53.34 kW) with insignificant variation in the overall efficiency (29.80–30.20%), at the obtained optimal solutions for the optimized dish concentrator configurations. Moreover, the results also emphasize how mirror soiling factor of the concentrator, has a dramatic effect on the optimal electric power and total efficiency of SDSS. It can be concluded that the proposed MOPSO approach can lead to more desired results and allow the technical feasibility for design of SDSS according to the need of such output power required for a certain application.